CRYPTOGAMS RICH NANOTHEROPHYTIC VEGETATION ON TRAVERTINE OUTCROPS NEAR TIVOLI - FANELLI, G. (Annali di Botanica, 2007)
An interesting community, Chaenorhino rubrifolii-Saxifragetum tridactylites ass. nova, referable to Alysso-Sedion albi is described from Bagni di Tivoli, near Rome. This community is very restricted, and occurs on travertine outcrops on extremely thin soil. Its composition is characterised by a rich cryptogamic layer, with interesting species such as Psora decipiens and Anoectangium aestivum, and a sparse herb layer composed by minute therophytes, such as Saxifraga tridactylites, Erophila verna, Chaenorhinum rubrifolium. The community is severely threatened and more effective measure of protection should be enforced on the area.